Asksia AI LOGO

Sia

Question
Math
Posted 8 months ago
Complete the recursive formula of the geometric sequence
1.5,6,24,96,.d(1)=d(n)=d(n1).
\begin{array}{l}
-1.5,6,-24,96, \ldots . \\
d(1)=\square \\
d(n)=d(n-1) .
\end{array}
Sign in to unlock the answer
Answer from Sia
Posted 8 months ago
Solution by Steps
step 1
Identify the first term of the geometric sequence
step 2
The first term of the sequence is 1.5-1.5, so d(1)=1.5d(1) = -1.5
step 3
Determine the common ratio by dividing the second term by the first term
step 4
The common ratio rr is 61.5=4\frac{6}{-1.5} = -4
step 5
Write the recursive formula using the first term and the common ratio
step 6
The recursive formula is d(n)=d(n1)rd(n) = d(n-1) \cdot r
step 7
Substitute the common ratio 4-4 into the recursive formula
step 8
The complete recursive formula is d(n)=d(n1)(4)d(n) = d(n-1) \cdot (-4)
Answer
d(1)=1.5d(1) = -1.5, d(n)=d(n1)(4)d(n) = d(n-1) \cdot (-4) for n>1n > 1
Key Concept
Geometric Sequence Recursive Formula
Explanation
The recursive formula for a geometric sequence is defined by the first term and the common ratio, which is the factor by which each term is multiplied to obtain the subsequent term.

Not the question you are looking for? Ask here!

Enter question by text

Enter question by image

Unlock Smarter Learning with AskSia Super!

Join Super, our all-in-one AI solution that can greatly improve your learning efficiency.

30% higher accuracy than GPT-4o
Entire learning journey support
The most student-friendly features
Study Other Question